Application of Botulinum Neurotoxin in Lower Urinary Tract Dysfunctions: Where Are We Now? (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Evidence has shown that botulinum toxin A has advantages in lower urinary tract dysfunctions (LUTDs), especially in interstitial cystitis, urethral sphincter dysfunction, and inflammatory bladder disorders which currently cannot be adequately treated with oral pharmacological medications. This Special Issue has collected original or review articles that focus on the novel applications of botulinum toxin A in LUTDs. The research has been updated and contains novel therapeutic applications of botulinum toxin for bladder or urethral dysfunctions. This Special Issue of Toxins provides current knowledge surrounding the status of botulinum toxin in functional urology and LUTDs.